Influence of Postconceptional Age on the Renal Biomarkers in Very-Low-Birth-Weight Infants - Ro Sie Lee; So Young Shin; Won Ho Jung; Jae Hyun Park (Korean Society of Neonatology, 2021)
Purpose We investigated whether consecutive levels of new emerging renal biomarkers, including serum cystatin C (CysC) and urinary neutrophil gelatinase-associated lipocalin (NGAL)/creatinine (Cr) ratio, were affected by postconceptional age in very-low-birth-weight (VLBW) infants. Methods Repeatedly measured samples for each infant were divided into four groups according to postnatal age: at birth (stage I), 3 to 7 days postnatally (stage II), 8 to 28 days postnatally (stage III), and >28 days postnatally (stage IV). The association between renal biomarkers and postconceptional age was assessed using Pearson's correlation coefficient, and the mean values of renal biomarkers in the four stages were compared using repeated-measures analysis of variance. Results For samples measured at birth, serum CysC (r=-0.358, P=0.032) and urinary NGAL/Cr ratio (r=-0.522, P=0.001) were negatively correlated with gestational age, whereas serum Cr (r=0.148, P=0.390) was not. In addition, for all samples measured, serum CysC (r=-0.209, P=0.012), urinary NGAL/Cr ratio (r=-0.536, P<0.001), and serum Cr (r=-0.311, P<0.001) were negatively correlated with postconceptional age. Compared with the mean values of the postnatal age-specific stages, serum CysC showed no significant differences in any of the four stages. However, the urinary NGAL/Cr ratio in stage IV was significantly different from those in stages I to III. Conclusion Although urinary NGAL/Cr ratio and serum CysC were negatively correlated with postconceptional age considering renal development, serum CysC showed no significant differences in any of the four postnatal age-specific stages. Urinary NGAL/Cr ratio at >28 days postnatally seems to be more affected by postconceptional age than serum CysC in VLBW infants.